Kedudukan Putusan Mahkamah Konstitusi Dalam Hukum Ketenagakerjaan (Kajian Terhadap Putusan Mahkamah Konstitusi No. 37/PUU-IX/2011) - Suparto, Suparto; Zulkifli, Zulkifli (Jurnal Hukum & Pembangunan, 2022)
Law Number 13 of 2003 concerning Manpower is one of the laws that is subjected to a judicial review to the Constitutional Court (MK). One of the reasons for filing a judicial review is that the application of Article 155 paragraph (2) has the potential to create legal uncertainty, given the absence of a clear interpretation of the clause " not yet defined ”. The Constitutional Court Decision No. 37 / PUU-IX / 2011 granted the petitioners' petition, and stated that the phrase "not yet established" was interpreted as "not yet legally binding". As a result, the process fee during the suspension period must be paid until the verdict has permanent legal force. This decision is felt to be burdensome for employers who will pay the process fee money while the workers do not do any work in the company, this is considered unfair by the employer. Then the Supreme Court issued a Supreme Court Circular (SEMA) Number 3 of 2015 and one of its contents was that after the Constitutional Court decision Number 37 / PUU-IX / 2011, entrepreneurs paid processing fees for 6 (six) months. Excess time in the process of the Industrial Relations Experience (PHI) as referred to in Law Number 2 of 2004 is no longer the responsibility of the parties. After the issuance of SEMA Number 3 of 2015, the process fee returns to the way it was before the issuance of the Constitutional Court Decision Number 37 / PUU-IX / 2011. So that the workers who are affected in this wage process experience legal uncertainty and feel disadvantaged.